MATHEMATICS LEARNING STRATEGY BOOK ON PEDAGOGICAL CONTENT KNOWLEDGE FOR ELEMENTARY SCHOOL PRE-SERVICE TEACHERS - Mukti Sintawati; Asih Mardati; Ginanjar Abdurrahman (Refleksi Edukatika, 2022)
The goal of this study is to describe the impact of a mathematics learning strategy book on elementary school pre-service teacher' pedagogical content knowledge.